La reinvención de lo público en la videocultura urbana - García Canclini, Néstor (Revista de Antropología Social, 2002)
¿Is it possible to reconstruct the public sphere in a megalopolis where the private sphere invades it all, where the rules are replaced by chaos, or by the apparent control of those who inform and watch? Since the traditional concepts of family, city and National State have drastically changed there is an attempt to redefine what is public in the new urban experiences established by the megacities and the mass media. The electronic media by constructing imaginaries which articulate the global and the local, as well as the urban visual publicity, through the spectacularization of goods and services, including those which only minorities have access to. This allows the question of whether the function of the media is pragmatic or ritual and symbolic.